Population of the Philippines by Islands, provinces, municipalities, and barrios taken in the Year 1903 - United States. Bureau of the Census ([United States Gobernment Printing Office, 1904)
The Philippine archipelago lies entirely within the Tropics, and numbers approximately 3,141 islands and islets, which extend from latitude 4 : 40' to 21° 10' north, and from east longitude 116 40' to 126° 34'. For the general configuration of the islands, and their more detailed topographic features, reference should be had to the maps and relief models prepared by the Rev. Jose Algue, 8. J., which form part of the Philippine exhibit at the Louisiana Purchase reposition. Within this area of 832,968 square miles of land and water dwells a population of 7,635,426 people. Of this number 6,987,686 are civilized, or partly so, while 647,740 are wild and uncivilized, although not without some knowledge of the domestic arts.
Electronic Reproduction.